Genetically predicted major depression causally increases the risk of temporomandibular joint disorders - Wu, Shiqian; Chen, Zhuo; Zhao, Yawen; He, Qiang; Yin, Zhongxiu; Yao, Hailiang; Liu, Huili; Yan, Lihui (Frontiers in Genetics, 2024)
Objective: Observational studies have reported that mental disorders are comorbid with temporomandibular joint disorder (TMD). However, the causal relationship remains uncertain. To clarify the causal relationship between three common mental illnesses and TMD, we conduct this Mendelian Randomization (MR) study.The large-scale genome-wide association studies data of major depression, bipolar disorder and schizophrenia were retrieved from the Psychiatric Genomics Consortium. The summary data of TMD was obtained from the Finn-Gen consortium, including 211,023 subjects of European descent (5,668 cases and 205,355 controls).The main approach utilized was inverse variance weighting (IVW) to evaluate the causal association between the three mental disorders and TMD. Five sensitivity analyses including MR-Egger, Maximum Likelihood, Weighted median, MR. RAPS and MR-PRESSO were used as supplements. We conducted heterogeneity tests and pleiotropic tests to ensure the robustness.As shown by the IVW method, genetically determined major depression was associated with a 1.65-fold risk of TMD (95% CI = 1.10 -2.47, P < 0.05). The direction and effect size remained consistent with sensitivity analyses. The odds ratios (ORs) were 1.51 (95% CI = 0.24 -9.41, P > 0.05) for MR-Egger, 1.60 (95% CI = 0.98 -2.61, P > 0.05) for Weighted median, 1.68 (95% CI = 1.19 -2.38, P < 0.05) for Maximum likelihood, 1.56 (95% CI = 1.05 -2.33, P < 0.05) for MR. RAPS, and 1.65 (95% CI = 1.10 -2.47, P < 0.05) for MR-PRESSO, respectively. No pleiotropy was observed (both P for MR-Egger intercept and Global test > 0.05). In addition, the IVW method identified no significant correlation between bipolar disorder, schizophrenia and TMD.Genetic evidence supports a causal relationship between major depression and TMD, instead of bipolar disorder and schizophrenia. These findings emphasize the importance of assessing a patient's depressive status in clinical settings.